Atributos físicos, químicos e qualidade de um Neossolo Regolítico sob cultivo de adubos verdes - Nascimento, Gislaine dos Santos (2021)
Inadequate management practices can negatively affect the soil chemical and, physical quality. In this context, sustainable alternatives can be adopted with the aim to improve the production systems quality without compromising the soil quality. Green manure becomes a viable alternative, since it contributes to increasing soil productivity without negative impacts to environment. Therefore, we aim was to evaluate the soil physical and, chemical attributes and, quality index of Regosol under cultivation of green manures in Agreste Paraibano. The experiment was carried out from July to December 2019, at the “Chã-de-Jardim” Experimental Station. The treatments were: Brachiaria decumbens, Crotalaria juncea, Crotalaria ochroleuca, Crotalaria spectabilis, jack bean (Canavalia ensiformis), Dolichos lablab, paearl millet (Pennisetum glaucum), velvet-bean (Stizolobium aterrimum), velvet-bean (Mucuna pruriens), and perennial soy (Neonotonia wightii) in a randomized block design, with three replicates. Undisturbed, and deformed soil samples were collected at two depths (0.0-0.1 and 0.1-0.2 m) to determine the following variables: 1) soil physical: soil bulk density, total porosity, soil macroporosity, soil microporosity, soil field capacity, available water content, permanent wilting point, soil aeration capacity, and soil available water capacity; 2) soil chemical and, fertility: soil pH, available phosphorus, exchangeable Ca, Mg and K, soil organic carbon, soil carbon stock, sum of bases, H+Al, cation exchange capacity (CEC), and base saturation. The shoot dry biomass production, root density, and soil quality index (SQI) were also evaluated. For data evaluation, one-way and two-way analysis of variance, Bonferroni test (p<0.05, 0.01, and 0.001), Pearson correlation analysis, redundancy analysis, and principal components analysis were performed. The SQI was calculated based on the sum of the indicator attributes (shoot and root biomass, available phosphorus, exchangeable Ca and K, and soil carbon stock), and the correction factor. The highest values of soil pH, exchangeable bases, CEC, and soil available water capacity were found in plots under Poaceae plants (e.g., B. decumbens and P. glaucum) cultivation, while the highest values of H+Al, CEC, soil available water, and soil available water capacity were found in plots where Fabaceae plants (e.g., C. ensiformis, C. juncea, C. ochroleuca, C. spectabilis, D. lablab, M. pruriens, N. wightii, and S. aterrimum) were cultivated. At the depth of 0,0-0,1 m, the highest values exchangeable Ca, Mg and K, sum of bases, base saturation, soil organic carbon, microporosity, soil porosity, and soil aeration capacity were found, while at the depth of 0.1-0.2 m there were higher values of soil pH, H+Al, bulk density, and permanent wilting point. The highest values for shoot dry biomass and root density, were found in the plots cultivated with C. ensiformis and N. wightii, respectively. All species used as green manure provided a significant (p<0.01) improvement in soil quality; however, the highest SQI value was found in plots cultivated with N. wightii. About 33 predictive models were developed to estimate the soil physical and chemical attributes, and plant biomass production for the conditions of this study.